Jurisprudential extracts on the appeal (Legal journal - Research in Legal and Social Sciences, 2017)
The objective of this article is to inform the officials of the Public Ministry of the criteria assumed by the Supreme Court of Justice in criminal matters. To this end, excerpts from resolutions of the Criminal Chamber are exposed in which extraordinary appeals of cassation are resolved. It should be noted that the summaries will be presented in a thematic manner and not only reflect the technical aspect of said resource, but also various issues on criminal procedural law and substantive criminal law. The appeal is an extraordinary remedy aimed at controlling the substantial accuracy of the sentence and its formal legitimacy, which is why it is an important tool to obtain legal certainty and equality before the law. In our country, this challenging means was incorporated into the legislation by the National Constitution of 1992, which, in its art. 269 ​​inc. 6, grants the Supreme Court of Justice the power to hear and resolve the cassation appeal in the manner and to the extent established by law. Likewise, the criminal cassation appeal is regulated in the Criminal Procedure Code, specifically from art. 477 to 480. The main characteristic of this resource is that it is not freely formulated, since it constitutes an eminently technical challenge.